A new integrative model for the co-occurrence of non-suicidal self-injury behaviours and eating disorder symptoms - Isabel Krug (BMC, 2021)
Abstract Objective The high co-occurrence of non-suicidal self-injury (NSSI) behaviours and eating disorder (ED) symptoms suggests these conditions share common aetiological processes. We assessed a new integrative model of shared factors for NSSI and ED symptoms, where affect dysregulation, impulsivity, self-esteem, and body dissatisfaction mediated the relationship between insecure attachment and maladaptive schemas and NSSI and ED symptoms. A further aim of the study was to assess whether the model behaved similarly across a clinical eating disorder (ED) and a community sample. Method 123 females with a lifetime ED diagnosis and 531 female individuals from the community completed an online survey, which included measures assessing the variables of interest. A cross-sectional single time point analysis was used. Results Invariance testing indicated that the model was structurally non-invariant (different across groups). The proposed integrative model was a good fit for the ED group, but for the community sample only a revised model reached an acceptable fit. Both attachment and maladaptive schemas, included early in the model, were implicated in the pathways leading to ED and NSSI symptoms in the ED and community groups. In the community group, impulsivity, a mediator, was a shared predictor for NSSI and bulimic symptoms. No other mediating variables were shared by NSSI and ED symptoms in the two groups. Overall, the proposed model explained slightly more variance for the ED group relative to the community group in drive for thinness (R 2  = .57 vs .51) and NSSI (R 2  = .29 vs .24) but less variance in bulimic symptoms (R 2  = .33 vs .39). Conclusion We conclude that the current model provides only limited support for explaining the comorbidity between NSSI and ED symptoms. It is vital to consider both common (e.g., attachment and maladaptive schemas) and specific factors (e.g., impulsivity) to better understand the pathways that lead to the co-occurrence of NSSI and ED symptoms. A new integrative model assessed whether emotion dysregulation, impulsivity, self-esteem, and body dissatisfaction were mediators in the relationship between insecure attachment and maladaptive beliefs about the world and the self and subsequent eating disorder and self-harm symptoms. A further aim was to assess whether the proposed model differed between a clinical eating disorder and a community sample. All participants were female and included 123 patients with a lifetime eating disorder and 531 individuals from the community. Participating individuals completed an online survey at one timepoint, which included measures assessing the variables of interest. The findings of the current study indicated that the proposed model was a good match for the clinical eating disorder sample, but for the community sample only a revised model yielded acceptable statistical fit. Both insecure attachment and maladaptive beliefs about the world and the self, included early in the model, were indirectly related to eating disorder and self-harm symptoms for both the eating disorder and the community groups. Impulsivity, a mediator, was the only shared predictor for self-harm, and bulimic symptoms in the community group. We conclude that the current model provides only limited support for explaining the comorbidity between self-harming behaviours and disordered eating symptoms.